Analysis of influence factors of social networks to prepare future engineers-teachers - Kuleshova, V.; Paiunova, A. (Problems of Engineer-Pedagogical Education, 2018)
Research devoted to the actual topic "Analysis of the impact factors of social networks for training future engineers-teachers." The results of Pilot study in the scientific training of professional and pedagogical institute Ukrainian Engineering and Pedagogical Academy (c. Bakhmut) among students of 2nd and 3rd year. The results of studies that show the dependence of future engineersteachers from social networks. Determined that the most popular social networks "VKontakte" and most of the students spend on social networks for several hours a day. The main reasons for the appeal is to the quick communication, searching for information and holding his leisure. These features of the training of future engineers, teachers. Investigated the advantages and disadvantages of social networks influence on students. The authors of this recommendation on ways to solve the problems associated with the use of social networks. Represented possibilities of virtual social networks for the needs of higher education.